2020
DOI: 10.1097/wnp.0000000000000777
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Neuromonitoring of Blink Reflex During Posterior Fossa Surgeries and Its Correlation With Clinical Outcome

Abstract: Purpose:Blink reflex (BR) under general anesthesia as an intraoperative neuromonitoring method was used to monitor facial nerves in few studies. This study aimed to test the utility of intraoperative BR during cerebellopontine angle and skull base surgeries, assess its prognostic value for facial nerve functions, and compare it with facial corticobulbar motor evoked potentials (CoMEPs).Methods:Blink reflex and facial CoMEPs were recorded from 40 patients undergoing skull base surgeries. Subdermal needles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This intraoperative BR recording method has been used in several studies to monitor trigeminal or facial nerve function during MVD and posterior fossa surgeries. [47][48][49] In this study, we found that the absence of R1 post was significantly associated with complete pain relief and facial numbness following PBC. Therefore, we consider that intraoperative monitoring of BR would be feasible during PBC, and that the absence of R1 may provide real-time feedback on the surgical effect and provide a reference point for terminating the compression.…”
Section: Discussionmentioning
confidence: 54%
“…This intraoperative BR recording method has been used in several studies to monitor trigeminal or facial nerve function during MVD and posterior fossa surgeries. [47][48][49] In this study, we found that the absence of R1 post was significantly associated with complete pain relief and facial numbness following PBC. Therefore, we consider that intraoperative monitoring of BR would be feasible during PBC, and that the absence of R1 may provide real-time feedback on the surgical effect and provide a reference point for terminating the compression.…”
Section: Discussionmentioning
confidence: 54%
“…BR is useful in the study of trigeminal and facial nerve lesions, peripheral neuropathy, posterior fossa lesions, multiple sclerosis, and extrapyramidal diseases [51]. Under general anesthesia in the operating room, only the R1 response can be recorded [52][53][54][55].…”
Section: Brainstem Reflexesmentioning
confidence: 99%